2013
DOI: 10.3109/00016357.2013.859728
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles in orthodontics, a review of antimicrobial and anti-caries applications

Abstract: Nanoparticles (NPs) are insoluble particles smaller than 100 nm in size. In order to prevent microbial adhesion or enamel demineralization in orthodontic therapy, two broad strategies have been used. These are incorporating certain NPs into orthodontic adhesives/cements or acrylic resins (nanofillers, silver, TiO2, SiO2, hydroxyapatite, fluorapatite, fluorohydroxyapatite) and coating surfaces of orthodontic appliances with NPs (i.e. coating bracket surfaces with a thin film of nitrogen-doped TiO2). Although th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
123
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(130 citation statements)
references
References 49 publications
1
123
0
6
Order By: Relevance
“…[8] Nanoparticles are incorporated into orthodontic adhesives/cements or acrylic resins and can coated onto the surfaces of orthodontic appliances to prevent microbial adhesion or enamel demineralization in orthodontic therapy. [9] Incorporating nanoparticles within the bonding agent and not into the adhesive body itself has weighed a more convincing accession and in some way profitable from a clinical outlook. Considering that the bonding agent which comes into candid touch with the enamel surface, the destination area for precautionary pursuits.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Nanoparticles are incorporated into orthodontic adhesives/cements or acrylic resins and can coated onto the surfaces of orthodontic appliances to prevent microbial adhesion or enamel demineralization in orthodontic therapy. [9] Incorporating nanoparticles within the bonding agent and not into the adhesive body itself has weighed a more convincing accession and in some way profitable from a clinical outlook. Considering that the bonding agent which comes into candid touch with the enamel surface, the destination area for precautionary pursuits.…”
Section: Introductionmentioning
confidence: 99%
“…-Antibacterial effect of the inert SiO 2 which is present in the S53P4 composition and may produce a coating on surrounding substrata [36]. -Physical damage to cell wall coming from S53P4 debris that could be related to its antibacterial effect [31].…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of fluoride in fluoride dentifrices varies from 0.025% (250 ppm F-) to 0.15% (1500 ppm F-), reaching even 0.50% (5000 ppm F-), for specific situations such as high caries risk patients [18,19]. Some studies have found that below 500 ppm F-there is no scientific evidence of a preventive effect.…”
Section: Use Of Fluoridementioning
confidence: 99%
“…Substances such quaternary ammonium methacrylates, dodecyl amine, bipyridine, tannic acid derivatives, polyhexanide, amphiphilic lipids, silver, sodium chloride gluconate, have been show improve the antibacterial effect and also shown ability to reduce restauration roughness, plaque retention and biofilm formation [18].…”
Section: Antimicrobial Usementioning
confidence: 99%